Private and local logics: an overview to the presence of extractives industries from the communities’ histories - Burneo, María Luisa (2013)
The present article discusses the way we approach the process of change in rural communities with active presence of extractive industries. As an example, it presents a study about a peasant community from the Peruvian northern coast where a petroleum extraction project is being developed. The case analysis suggests that, in such contexts, different and conflicting patterns of resource, such as land usage, valuation, access and appropriation are configured, leading to a very complex scenario for the decision making process about the future of these resources. The article thus states that categories such as social-environmental management, conflict resolution, and negotiation can lead to a simplified interpretation of reality. In this sense, by presenting some critical issues, it argues the importance of adopting anthropological and sociological approaches in order to consider the way spatiality and temporality are being conceived, as well as to integrate the historical process of land appropriation into the analysis.